Effect of conjugated structures of bipyridinium cations on ion assembly and charge-transfer of their tetrathiafulvalene-bicarboxylate salts. Issue 11 (19th February 2016) - Huo, Peng; Li, Yan-Hong; Xue, Li-Jun; Chen, Ting; Yu, Lei; Zhu, Qin-Yu; Dai, Jie
Abstract : This is a systematic study of the effect of different π-conjugated systems on charge-transfer properties in terms of crystal structures. The results demonstrate a synergistic effect of native cation–anion charge-transfer ability and interion interactions based on a structural arrangement. Abstract : A series of tetrathiafulvalene (electron donor, D) charge-transfer salts with three methyl bipyridiniums (electron acceptor, A) in the basic formulas MV(HL)2 (1 ), MeBpe(HL)2 (2 ) and MeBpa(HL)2 (3 ) (L = dimethylthio-tetrathiafulvalene-bicarboxylate, MV = methyl viologen, MeBpe = 1, 2-bi(4-pyridinium) ethene and MeBpa =1, 2-bi(4-pyridinium) ethane) was synthesized and their structures were characterized by X-ray single crystal analysis. The three bipyridiniums allow the exploration of the effect of different conjugated systems on molecular packing and charge-transfer interactions. A type of –DDDD– stacking column with edge-to-edge short D⋯A⋯D contacts is found in MV compound1, while in π-extended MeBpe compound2, a –DADDAD– type of stacking column with face-to-face short D⋯D and A⋯D stacking is formed, which shows the most effective cation–anion interaction. No effective interaction is found for the non-conjugated MeBpa compound3 . The charge-transfer from an anion to a cation measured by UV-vis, CV and ESR is in the order of2 >1 ≫3, which is greatly in accordance with the order of the cation's conjugated state and CT interaction. It is known that charge-transfer is a key factor in obtaining photoelectric materials. Photocurrent responses of these compounds are consequently studied and the results agree with the intensity of charge-transfer. This is a systematic study of the effect of different π-conjugated systems on charge-transfer properties in terms of crystal structures.